The role of fibrinogen plasma levels, the –455G>A fibrinogen and the factor XIII A subunit (FXIII-A) Val34Leu polymorphism in cancer-associated venous thrombosis - Tiedje, Vera; Dunkler, Daniela; Ay, Cihan; Horvath, Birgit; Quehenberger, Peter; Pabinger, Magdalena; Zielinski, Christoph; Pabinger, Ingrid; Mannhalter, Christine (Thrombosis and Haemostasis, 2011)
Venous thromboembolism (VTE) is a life-threatening complication in cancer patients. Identification of risk factors has been in focus in the past years. Functional single nucleotide polymorphisms (SNP) of coagulation factors known to influence the concentration or function may be considered to influence the risk of VTE in cancer patients. We evaluated the influence of fibrinogen plasma levels, the –455G>A SNP in the fibrinogen beta gene and the Val34Leu (163G>T) SNP in the factor XIII A-subunit (FXIII-A) gene on the risk of VTE. In 1,079 tumour patients recruited for the prospective Vienna Cancer and Thrombosis Study (CATS) fibrinogen levels were determined by the Clauss method. The FXIII-A Val34Leu and the fibrinogen –455G>A SNPs were tested by allele-specific PCR. The median follow-up time was 604 days, 83 thrombotic events occurred. The median fibrinogen level was 381 mg/dl (25th-75th percentile: 312 to 467). In a multivariable Cox model adjusted to chemotherapy, surgery, radiotherapy, age and sex, neither the fibrinogen concentration (hazard ratio [HR] =1.05, confidence interval [CI] 0.839–1.310 p=0.68), nor the –455G>A SNP (HR=0.77, 95%CI 0.491–1.197; p=0.24), nor the Val34Leu SNP (HR=0.99, 95%CI 0.646–1.542 p=0.99) were associated with occurrence of VTE. The fibrinogen concentration was not significantly different among the fibrinogen –455G or A genotype carriers (p = 0.33). Disseminated intravascular coagulation was observed in only five patients, none of these developed VTE. In conclusion, fibrinogen plasma levels, the fibrinogen –455G>A and the FXIII-A Val34Leu polymorphisms were not associated with VTE in our study.
Keywords: Venous thromboembolism; cancer; fibrinogen; factor XIII-A Val34Leu SNP; fibrinogen –455G>A SNP